PENGARUH BRAIN EXERCISE TERHADAP KEMAMPUAN KOGNITIF PADA LANSIA DI WILAYAH KERJA PUSKESMAS BANGGAE 1 KABUPATEN MAJENE - Weni Anggraeni; Ika Muzdalia; Irna Megawaty; Muh Amin; Juli Ayu Lestari (Jurnal Ilmiah Keperawatan, 2024)
Abstrack The final stage of human development is old age, where many changes occur, including significant physical, cognitive, psychological, and social changes experienced by elderly people over 60 years old. Brain exercise is a non-pharmacological technique to improve cognitive function. Brain exercise is a method to improve cognitive function in the elderly so that it can affect better cognitive function. The aim of this study was to determine the effect of brain exercise on cognitive abilities in the elderly. The type of research used in this research is quasi-experimental, using a pre- and post-test approach without control. The number of samples from 31 respondents was selected by sampling technique, namely accidental sampling. Data analysis using univariate and bivariate results of the Wilcoxon Test found that the p-value was 0.007 (p <0.05). The conclusion is that there is a significant effect of brain exercise on cognitive abilities in the elderly in the working area of the Banggae 1 Health Center, Majene Regency. Keywords: Elderly, Cognitive Function, Brain Exercise